Synthesis of Nanoscale Zero-Valent Iron with Polyphenol Extract from Cloves (Syzygium aromaticum) Through a Stepwise Reaction and Adsorption Test on Pb(II) - Yuliana Dewi Anugrah; Annissa Amalia; Salma Fitri Annisa (Chemistry and Materials, 2023)
Polyphenols from clove extract (Syzygium aromaticum) were successfully used as reducing agents to synthesize nanoscale zero-valent iron (nZVI). Optimization of nZVI synthesis was carried out by reacting polyphenols and FeSO4 at a composition of 0.25:4.75, 1:4, 2:3, and 3:2. The particle size analyzer showed that the smaller particle size distribution was obtained at nZVI 0.25:4.75, with values of D10 = 85.1 nm, D50 = 122 nm, and D90 = 175 nm. The results of the Pb(II) removal test showed that nZVI 0.25:4.75 had a fairly high percentage of Pb(II) removal, which was 96.4852% at 60 minutes. The smaller particle size of nZVI 0.25:4.75 compared to other samples is an important factor affecting the adsorption activity of Pb(II) in an aqueous medium.